A super enhancer controls expression and chromatin architecture within the MHC class II locus - Majumder, Parimal (J Exp Med, 2019)
Super enhancers (SEs) play critical roles in cell type–specific gene regulation. The mechanisms by which such elements work are largely unknown. Two SEs termed DR/DQ-SE and XL9-SE are situated within the human MHC class II locus between the HLA-DRB1 and HLA-DQA1 genes and are highly enriched for disease-causing SNPs. To test the function of these elements, we used CRISPR/Cas9 to generate a series of mutants that deleted the SE. Deletion of DR/DQ-SE resulted in reduced expression of HLA-DRB1 and HLA-DQA1 genes. The SEs were found to interact with each other and the promoters of HLA-DRB1 and HLA-DQA1. DR/DQ-SE also interacted with neighboring CTCF binding sites. Importantly, deletion of DR/DQ-SE reduced the local chromatin interactions, implying that it functions as the organizer for the local three-dimensional architecture. These data provide direct mechanisms by which an MHC-II SE contributes to expression of the locus and suggest how variation in these SEs may contribute to human disease and altered immunity.